Monuments of the Classical Antique Architecture as the Object of a Museum Exposition. The Open Storage of the Department of Classical Antiquities at the Restoration and Storage Centre “Staraia Derevnia” - Eremeeva, Anna A. (Actual Problems of Theory and History of Art, 2018)
In December 2015 five new galleries of the Department of Classical Antiquities were opened at the Hermitage Restoration and Storage Centre “Staraia Derevnia” (Old Village), including a room devoted to ancient architectural details, the so-called “Classical Antique Architecture”. Previously the exhibits were deposited at the New Hermitage, in the storage rooms that were unattended by the visitors. Now the exhibits are available for research by not only the specialists, but also by schoolchildren, students and all those who admire and study ancient history, architecture, archaeology and epigraphy. The room contains antique architectural details that date back to the period from the 4th century BC to the 4th century AD from Olbia, the Bosporan Kingdom, Chersonese, and Nymphea. The exposition is designed as a presentation of the ruins of ancient buildings, but supported with contemporary exhibition equipment and lighting. The open depository “Ancient Architecture” in the Restoration and Storage Centre of “Staraia Derevnia” is the new type of the art exhibition in the museum with classical traditions and interior limitations.
Keywords: architecture; museology; Classical archaeology; epigraphy; museum depositories